Family-Based Early Intervention Based on Family Outcomes for Families with Children with Multiple Disabilities - Ashri Maulidina, Citra (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2023)
This study aims to formulate a family-based early intervention program for parents who have children with Multiple disabilities based on Family Outscomes. The background of this study is the lack of family information related to the identification of children with multiple disabilities, family confusion in handling children who experience multiple disabilities, and the absence of family confidence in the situation of their children in the social environment. The subjects in this study were parents who had Children with Multiple Disabilitiesin this case were children with Cerebral Palsy who experienced obstacles in motor, cognitive, social & emotional, and language aspects and intellectual barriers. This research approach is a qualitative approach with three stages of research, namely assessment, validation, and implementation. The result of this study is an increase in family understanding of the child's condition, the occurrence of stimulation carried out by the family to the child, the family has begun to want to socialize their children in the surrounding social environment. The results and discussion of further research are discussed in this study.